2013
DOI: 10.1088/0953-8984/25/33/335804
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance identification of hydrogen at a zinc vacancy in ZnO

Abstract: Hydrogen (H) at a zinc vacancy (V Zn ) in ZnO is identified by electron paramagnetic resonance (EPR) and electron spin echo envelope modulation (ESEEM). In ZnO irradiated by 2 MeV electrons, a doublet EPR spectrum, labelled S1, was observed. The doublet structure and the accompanied weak satellites are shown to be the allowed and forbidden lines of the hyperfine structure due to the dipolar interaction between an electron spin S=1/2 and a nuclear spin I=1/2 of 1 H located at a V Zn . The involvement of a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The peak shape is also highly symmetrical and totally different from the asymmetric feature from ionized V O and Zn i defects with g factors less than 2 . We therefore assign it to the ionized V Zn defect, which has been identified as the g factor between 2.0018 and 2.056. Since V Zn is a surface-sensitive defect in ZnO, , mild vacuum annealing can modify the surface structure of NCs with high specific surface and lead to the formation of V Zn defects. We have further analyzed the introduction of V Zn defects by using PL and Raman spectra in Figure S5 as well as the positron annihilation lifetime spectra in Figure S8.…”
Section: Resultsmentioning
confidence: 95%
“…The peak shape is also highly symmetrical and totally different from the asymmetric feature from ionized V O and Zn i defects with g factors less than 2 . We therefore assign it to the ionized V Zn defect, which has been identified as the g factor between 2.0018 and 2.056. Since V Zn is a surface-sensitive defect in ZnO, , mild vacuum annealing can modify the surface structure of NCs with high specific surface and lead to the formation of V Zn defects. We have further analyzed the introduction of V Zn defects by using PL and Raman spectra in Figure S5 as well as the positron annihilation lifetime spectra in Figure S8.…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, if the spin localizes on the axial O, the symmetry of the system remains C 3v . Experimentally both of these cases have been observed in the work of Galland and Herve [43] and the V Zn EPR center was also studied by Son et al [44], who identified a separate center with H attached to the O in the V Zn . Here, we only discuss the V Zn .…”
Section: G-tensormentioning
confidence: 83%
“…[31,42] Aside from the intended incorporation of foreign ions, ZnO exhibits color center defects [43] , oxygen interstitial sites [44,45] and hydrogen defects [46,47] as naturally occurring defects at ambient conditions. Even though hydrogen defects have been evidenced experimentally by IR [48] , RAMAN [49] , EPR [50] and optical spectroscopy [51] and have been studied by quantum chemical calculations, [52,53] it is not clear if the concentration of these defects is high enough to have any impact on catalytic activity. With respect to solid-state 1 H NMR, two different 1 H NMR signals, including a fairly sharp signal at ~4.3 ppm, were observed in ZnO and ZnO:Al, which were claimed to correspond to interstitial H positions or the particle surface.…”
Section: Introductionmentioning
confidence: 99%